2013
DOI: 10.1177/1087057113500812
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Screening with Human iPS Cell–Derived Cardiomyocytes: HTS-Compatible Assays for Interrogating Cardiac Hypertrophy

Abstract: A major hurdle for cardiovascular disease researchers has been the lack of robust and physiologically relevant cell-based assays for drug discovery. Derivation of cardiomyocytes from human-induced pluripotent stem (iPS) cells at high purity, quality, and quantity enables the development of relevant models of human cardiac disease with source material that meets the demands of high-throughput screening (HTS). Here we demonstrate the utility of iPS cell-derived cardiomyocytes as an in vitro model of cardiac hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 37 publications
3
54
0
Order By: Relevance
“…To recapitulate sympathetic overstimulation, we exposed EHM to NE at clinically relevant concentrations (0.001–1 μmol/L) for 7 days. We also included a group of EHM exposed to endothelin-1 (0.01 μmol/l), a well established inducer of cardiomyocyte hypertrophy via the alternative Gq-protein transduction pathway 41 . Similarly as observed in patients, chronic NE stimulation induced contractile dysfunction in a concentration dependent manner (Figure 4a) with desensitization to acute β-adrenergic stimulation (Figure 4b), which according to its underlying mechanism only occurred under NE and not ET-1.…”
Section: Resultsmentioning
confidence: 99%
“…To recapitulate sympathetic overstimulation, we exposed EHM to NE at clinically relevant concentrations (0.001–1 μmol/L) for 7 days. We also included a group of EHM exposed to endothelin-1 (0.01 μmol/l), a well established inducer of cardiomyocyte hypertrophy via the alternative Gq-protein transduction pathway 41 . Similarly as observed in patients, chronic NE stimulation induced contractile dysfunction in a concentration dependent manner (Figure 4a) with desensitization to acute β-adrenergic stimulation (Figure 4b), which according to its underlying mechanism only occurred under NE and not ET-1.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore asked whether BET bromodomain inhibition could block pathologic cardiomyocyte hypertrophy in human cells. We tested the effects of JQ1 in a widely used human induced pluripotent stem cell–derived cardiomyocyte (iPSC-CM) culture system that originated from an iPSC line derived from a healthy human donor [iCell Cardiomyocytes, Cellular Dynamics International Inc. (CDI)] (48). Previous studies have demonstrated that these cells can mount a hypertrophic response to 10 nM endothelin-1 (ET-1) (48).…”
Section: Resultsmentioning
confidence: 99%
“…6C) and other typical marker genes induced in human iPSC-CMs during ET-1 stimulation (fig. S5A) (48). Quantitative enzyme-linked immunosorbent assay (ELISA) confirmed that JQ1 attenuated the ET-1–stimulated increase in BNP protein abundance (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Adaptation of this hypertrophy assay to 384-well plates will facilitate expanded screening efforts. Furthermore, this approach could be employed with iPS-derived cardiac myocytes [21], although optimized culture methods will likely be needed to maximize the responses of these cells to hypertrophic agonists [22]. …”
Section: Discussionmentioning
confidence: 99%